Transnasal Endoscopic Orbit and Optic Nerve Decompressions - Bleier, Benjamin S.; Müller, Sarina Katrin (Transnasal Endoscopic Skull Base and Brain Surgery. Surgical Anatomy and its Applications, 2nd edition, 2019)
Although endoscopic orbital and optic nerve decompression have been technically feasible for over three decades, their indications and extent of surgery continue to be a subject of debate. The most common indication for orbital decompression is dysthyroid orbitopathy resulting from Graves' disease. Other indications include intra- and extraconal tumors. The goals of surgery are to decrease intraocular pressure, reduce proptosis, or provide access to intraorbital pathologies. The degree of lamina papyracea and orbital floor removal, as well as the use of adjunctive lateral decompression and orbital fat resection, must be tailored to the patient's disease. Optic nerve decompression involves removal of the bone of the optic strut and canal.
CRIS-Team WoS Importer:2020-12-04